Studying the mechanical behavior of notched wood beams using full-field measurements. (15th April 2016) - Toussaint, E.; Fournely, E.; Moutou Pitti, R.; Grédiac, M.
Graphical abstract: Highlights: Notched beams are subjected to four-point bending tests. Full-field measurements allow to characterize the behavior of elements of beams. High gradient strain zones are clearly defined. Displacement and strain fields clearly depend on annual ring orientations of wood. Experimental maps are compared to numerical maps obtained with FE simulations. Abstract: This study focuses specifically on the mechanical behavior of notched timber beams and more generally on the existence of tensile stresses perpendicular to the grain, as well as shear in wood elements. The study presented here is based on full-field measurements to characterize the behavior of thin elements of a standardized beam. Experiments were carried out with a classic loading device and LVDT measurements as well as the grid method, which provides full-field displacement and strain measurements on the surface of the specimen. Tests were conducted for two orientations of the annual rings of the wood. Variations in the strain maps in the zone affected by shear and tensile stresses are analyzed, and the difference in response between specimens is pointed out, particularly with respect to ring orientations. Finally, the specimen is modeled using finite element software for comparison purposes. The constitutive material is linear elastic homogeneous, with elastic parameters obtained from ultrasonic experimentation. Our results exhibit the limit of this homogeneity hypothesis in notched zones.